Determination of the strain-energy release rate of a composite laminate under high-rate tensile deformation in fibre direction - Hoffmann, Justus; Cui, Hao; Petrinic, Nik (Elsevier, 2018)
In order to successfully model design-critical impact loading events on laminated composite structures, the rate-dependency of the composite material has to be correctly reflected. In this context, the rate-dependency of the strain-energy release rate for fibre tensile failure under high-rate loading conditions has not yet been satisfyingly explored. This study employed compact tension specimens consisting of IM7/8552 for dynamic testing on a split-Hopkinson tension bar system. Data reduction was based on the area method . The obtained strain-energy release rate for testing under high-rate conditions was determined to View the MathML sourceGIc,dynf+=82.0±20.8kJ/m2, exhibiting a salient drop compared to its counterpart obtained under quasi-static loading (View the MathML sourceGIc,QSf+=195.8±18.0kJ/m2). Analysis of the strain field surrounding the crack tip using digital image correlation (DIC) suggested a more extensive damage zone for testing under quasi-static than for high-rate loading. A fractographic analysis of the specimens did not indicate any pronounced difference in terms of fracture surface morphology across the two loading rate regimes.
Keywords: (A) Polymer-matrix composites (PMCs); (B) Fracture toughness; (D) Fractography; (D) Scanning electron microscopy (SEM); Fibre failure